Competitive Equilibrium Under Uncertainty - Radner, Roy (Econometrica, 1968)
The paper represents an application of the modern theory of competitive equilibrium to the case of uncertainty. Two theorems are presented: the first sets forth sufficient conditions for the existence of a competitive equilibrium for the case in which each economic agent has a given structure of information available and the second sets forth sufficient conditions for the existence of a competitive equilibrium for the case in which any available structure of information may be used. However, if the costs of obtaining information are included in the analysis, the conditions of the theorem may not be met. This is also true if the costs necessary to perform computations are included. In addition if part of the information available to economic agents concerns the behavior of other agents rather than concerning environmental variables, the conditions of the theorem may not be fulfilled. (Author)